Human rights and secularism in conflict with Hindutva: the Water controversy - Amit Singh (Antropologia Portuguesa, 2023)
This article analyses tension between human rights (including secularism) and Hindutva, the Hindu nationalists’ discourse. Particular focus is put on women’s rights and the right to freedom of expression and dissent in India using the film Water and the controversy associated with it in the north Indian district of Varanasi in 2000. Firstly, the relation between human rights, secularism and Hindutva/Hindu nationalism is discussed conceptually. This is followed by a discussion of the narratives of Hindutva’s followers in Varanasi and their involvement in the controversy surrounding the film Water. Extracts from interviews of Hindu nationalists are included to illustrate this tension. The article concludes by claiming that Hindutva is an antithetical to secularism and human rights.